Hybrid beamforming for downlink multiuser millimetre wave MIMO-OFDM systems - Zhang, Didi; Wang, Yafeng; Li, Xuehua; Xiang, Wei (IET communications, 2019)
In this study, the authors consider multi-user millimetre wave (mmWave) multiple-input multiple-output (MIMO) downlink communications for multi-carrier scenarios, e.g. orthogonal frequency-division multiplexing (OFDM) a common analogue precoder and combiner for the transmitter and receiver to maximise spectral efficiency is the main challenge for multi-carrier MIMO systems, they propose two methods to solve this problem. The first method designs the analogue precoder and combiner based on the channel average of all subcarriers, which helps reduce computational complexity. Moreover, the channels of all subcarriers can be viewed as a third-order tensor, and the second method is based on tensor unfolding, which makes full use of the channel information of all subcarriers. When the common analogue precoder and combiner are fixed, they consider designing a digital precoder to maximise the signal-to-leakage-plus-noise ratio of each user in every subcarrier, which leads to closed-form solutions compared with the block diagonal method. Simulation results demonstrate that the performance of the proposed methods is close to that of the fully digital precoding method, and increasing the number of RF transceiver chains helps improve the performance of the proposed methods.